1983
DOI: 10.1080/00327488308068743
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Hagfish Slime Gland Secretions: Partial Characterization of the Mucous Vesicle Fraction

Abstract: This paper deals with the collection, fractionation and partial characterization of the slime gland secretion of the Pacific hagfish (Eptatretus stouti) with emphasis on the mucous fraction. Secretions were collected by electrical stimulation of the glands of anesthetized hagfish and, using three different methods, separated into three fractions: 1) the thread cells, 2) the mucous vesicles of the mucous cells, and 3) the soluble fraction. The methods take advantage of the stabilization of the thread cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…While little is known about hagfish slime mucin material properties, chemical analyses suggest that they may have distinct physical properties. Typical vertebrate mucins contain up to 85% carbohydrate by dry mass but hagfish mucins contain only 12% (Salo et al, 1983). It is possible that the properties of the mucins have been shaped by selection to optimize their ability to transmit hydrodynamic forces to thread skeins.…”
Section: A New Model Of Hagfish Slime Deployment and Structurementioning
confidence: 99%
“…While little is known about hagfish slime mucin material properties, chemical analyses suggest that they may have distinct physical properties. Typical vertebrate mucins contain up to 85% carbohydrate by dry mass but hagfish mucins contain only 12% (Salo et al, 1983). It is possible that the properties of the mucins have been shaped by selection to optimize their ability to transmit hydrodynamic forces to thread skeins.…”
Section: A New Model Of Hagfish Slime Deployment and Structurementioning
confidence: 99%
“…Vesicles can be stabilized in concentrated (1 mol l −1 or higher) solutions containing polyvalent anions such as citrate, sulfate and phosphate, but appear to rupture in solutions containing monovalent anions, regardless of the valency of the associated cation (Luchtel et al, 1991;Salo et al, 1983). Based on these observations, Luchtel et al (Luchtel et al, 1991) hypothesized that ions from seawater enter the vesicle down their concentration gradients, resulting in an influx of water and the swelling and rupture of the vesicle.…”
Section: Introductionmentioning
confidence: 99%
“…The exudate combines with seawater to form slime, an effective defense mechanism because of its ability to lodge on gills and impair respiration (Lim et al, 2006;Zintzen et al, 2011). The exudate consists of two principal components, long (~up to 15 cm), thin (~1-3 μm wide) protein threads and mucin-like glycoproteins (Luchtel et al, 1991;Salo et al, 1983). Recent findings have demonstrated that during mixing of slime exudate with seawater, the mucins elongate into strands and assist in the unravelling of condensed slime threads .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The other main component, the mucin vesicles contain mucin-like glycoproteins, which are negatively charged by sulphonated side groups. [6][7][8] Once in contact with seawater, the mucin vesicles swell, rupture, and discharge their mucin. 9 The hydrated mucin and the network of unraveled skeins synergistically form hagfish slime (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that a charged gel with a complex network structure rapidly deploys in a strongly charge-screening environment as in seawater (ionic strength of about 0.7 M 12 ) is intriguing and has led to studies that investigated the effects of ionic strength and ionic composition. The main areas of focus comprised the effects of salts on ex vivo stabilization of hagfish exudate, 8,[13][14][15] skein unraveling, 16,17 mucin vesicle swelling and rupture, 9,[16][17][18] swelling and hydration of skeins 19 and reconstituted biomimetic materials made from slime thread proteins, 20 and whole hagfish slime functionality. 17 These studies show (i) that a high osmolarity of about 800 mOsmol l À1 and higher achieved by divalent anions (sulfate, citrate, phosphate) stabilizes hagfish exudate, 8,14,15 (ii) that seawater assists the dissolution of a glue, which holds the native skeins together and mediates unraveling, 16 (iii) that protein threads and materials made from those protein swell less in high osmolarity environments, 19,20 (iv) that viscosities of mucin solutions are lower in seawater than in deionized water, 11,17 and (v) that swelling and rupture of hagfish mucin vesicles requires the presence calcium ions when the ionic strength of the solution is 4100 mM.…”
Section: Introductionmentioning
confidence: 99%